PKM PENINGKATAN PRODUKTIVITAS KELOMPOK USAHA PEMBUAT KULINER KHAS BANGKA - Boy Rollastin; Yuliyanto Yuliyanto; Yang Agita Rindri (Jurnal Pengabdian Masyarakat Polmanbabel, 2021)
There are many indigenous cuisines of the Belinyu community, such as: Pempek (Kelesan), grilled satay (otak-otak), Model, Lenggang, Tekwan etc. These cuisines come from the processing of seafood and become targets of travelers for culinary hunting. Based on the results of surveys to several places in the Belinyu sub-district, most of these culinary craftsmen are home industries. They still process the food, especially the dough manually. This process affects the quality of the dough, which becomes uneven and hard. The dough is also difficult to become smooth. To make the dough smooth using this manual method, it will take a long time to stir in the stirring process. This causes delays in production time. The specific target of this community service activity is the establishment of a mutually beneficial relationship between Polman Babel and Partners. Partners will receive appropriate technical assistance in the form of mixer machines and production business management training. In order to solve the production problem, such as the quality and production capacity that must be achieved, an appropriate technology was made. The technology is a mixer machine with a dough capacity of 5 Kg/operation or 25 kg/hour using electromotor power. This machine is expected to solve the production problems faced by partners.